2014
DOI: 10.1002/aic.14693
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to determine wet restitution coefficients through a unified correlation and energy analysis

Abstract: Wet particle interactions are observed in many applications, for example, pharmaceutical, food, agricultural, polymerization, agglomeration, and coating, in which an accurate evaluation of the wet restitution coefficient (ewet) is crucial to understand the particle flowability, operating conditions and product size distribution. Experiments were performed to measure the wet restitution coefficient by impacting a spherical particle on a stationary plate covered with a thin liquid layer of water or glycerol solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…With further increase in the relative collision velocity, e wet showed a steep increase, followed by a gradual increase. This result is qualitatively consistent with an experimental result of collision between a particle and a liquid film, reported in Sutkar et al (2015). From our simulation result, the velocity criterion for the particle adhesion v c was determined as 2.9 m/s.…”
Section: Adhesion Of Two Colliding Particles By Dynamic Liquid Bridgesupporting
confidence: 85%
See 1 more Smart Citation
“…With further increase in the relative collision velocity, e wet showed a steep increase, followed by a gradual increase. This result is qualitatively consistent with an experimental result of collision between a particle and a liquid film, reported in Sutkar et al (2015). From our simulation result, the velocity criterion for the particle adhesion v c was determined as 2.9 m/s.…”
Section: Adhesion Of Two Colliding Particles By Dynamic Liquid Bridgesupporting
confidence: 85%
“…Collision between a spherical particle and a stationary liquid film was experimentally analyzed Davis, 2004, 2006;Antonyuk et al, 2009;Sutkar et al, 2015). Antonyuk et al (2009) revealed that at higher viscosity and thicker liquid layer, particle kinetic energy was more likely to be dissipated, indicating that these properties need to be large to enhance agglomeration rate.…”
Section: Introductionmentioning
confidence: 98%
“…A purely elastic contact between rock particles accompanied by energy dissipation was studied in [26]. The energy dissipation rates of wet particles were determined for five distinct collision phases [27].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, when a liquid film is applied, the particle size can have a significant effect on the energy dissipation during wet collisions. The reason for this behaviour has been explained by many researchers, that is, all damping forces (such as surface tension force, drag force, viscous force) depend on the particle diameter either via a power law or by a linear relationship. This is confirmed by the results shown in Figure , which shows the wet restitution coefficient ewet,n as a function of particle diameter d p for a sphere impacting on a 200 μm liquid layer at an impact velocity v im = 1.3 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Kantak et al proposed a simple model on the basis of their experimental data, ewet=edry(1Stc/St), with e dry the restitution coefficient under dry conditions. Recently, Sutkar et al developed an energy balance model for the estimation of e wet in terms of well‐known dimensionless numbers, such as the liquid Reynolds number, Stokes number, and Weber number.…”
Section: Introductionmentioning
confidence: 99%